IFNγ-stimulated dendritic cell extracellular vesicles can be nasally administered to the brain and enter oligodendrocytes. - Kae M Pusic (Public Library of Science (PLoS), 2021)
Extracellular vesicles secreted from IFNγ-stimulated rat dendritic cells (referred to here as IFNγ-DC-EVs) contain miRNAs which promote myelination (including but not limited to miR-219), and preferentially enter oligodendrocytes in brain slice cultures. IFNγ-DC-EVs also increase myelination when nasally administered to naïve rats. While we can infer that these extracellular vesicles enter the CNS from functional studies, here we demonstrate biodistribution throughout the brain after nasal delivery by way of imaging studies. After nasal administration, Xenolight DiR-labelled IFNγ-DC-EVs were detected 30 minutes later throughout the brain and the cervical spinal cord. We next examined cellular uptake of IFNγ-DC-EVs by transfecting IFNγ-DC-EVs with mCherry mRNA prior to nasal administration. mCherry-positive cells were found along the rostrocaudal axis of the brain to the brainstem. These cells morphologically resembled oligodendrocytes, and indeed cell-specific co-staining for neurons, astrocytes, microglia and oligodendrocytes showed that mcherry positive cells were predominantly oligodendrocytes. This is in keeping with our prior in vitro results showing that IFNγ-DC-EVs are preferentially taken up by oligodendrocytes, and to a lesser extent, microglia. To confirm that IFNγ-DC-EVs delivered cargo to oligodendrocytes, we quantified protein levels of miR-219 mRNA targets expressed in oligodendrocyte lineage cells, and found significantly reduced expression. Finally, we compared intranasal versus intravenous delivery of Xenolight DiR-labelled IFNγ-DC-EVs. Though labelled IFNγ-DC-EVs entered the CNS via both routes, we found that nasal delivery more specifically targeted the CNS with less accumulation in the liver. Taken together, these data show that intranasal administration is an effective route for delivery of IFNγ-DC-EVs to the CNS, and provides additional support for their development as an EV-based neurotherapeutic that, for the first time, targets oligodendrocytes.